Comparison Between The Effects of Betamethasone Gel And Lidocaine Jelly To Reduce PostOperative Tracheal Tube Related Airway Symptoms - Alam, Syed Sajjad; Abbas, Nighat; Asghar, Ali; Rafique, Muhammad; Abid, Khadijah (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the role of betamethasone gel and lidocaine jelly on reducing the post-operative airway complications related to tracheal tube. Study Design: Comparative prospective study. Place and Duration of Study: Department of Anesthesia, Liaquat National Hospital, from Jul 2019 to Jan 2020. Methodology: A total of 150 patients were randomly assigned into three different groups; group-B (0.05% betamethasone gel), group-L (tube lubricated with 2% lidocaine jelly) and group-C (intubated with un-lubricated tubes). Patients were assigned by using lottery method, which was carried out by a research assistant who was not involved in the study. There were 50 patients in each group. Results: Post-operative sore throat and post-extubation cough at 24-hours were statistically insignificant (p>0.05) between groups while hoarseness of voice at 24-hours postoperatively was significant (p<0.05) in all the groups. The overall difference for severity of postoperative sore throat, hoarseness of voice and post-extubation cough at24 hours in the groups B, L, and C were statistically significant (<0.05). Conclusion: The application of betamethasone gel on endotracheal tube before intubation reduces the post-extubation cough, severity of post-operative sore throat, hoarseness of voice and post-extubation cough in comparison with the application of lidocaine jelly and un-lubricated ETT.